设矩阵A=[img=296x296]17d60e88f05f26f.png[/img],则A*中位于第1行第2列的元素是( )
A: 3
B: -6
C: -3
D: 6
A: 3
B: -6
C: -3
D: 6
举一反三
- 设f(x)=x(x-1)(x-2)(x-3),则f’(0)=() A: -6 B: -2 C: 3 D: -3
- 设f(x)=[img=50x19]17e0bb9e8343c64.jpg[/img]则f[f(1)]=__________. A: 0 B: 1 C: 2 D: 3
- 设 f(x)=1-2x,g(f(x))=(1-x)/x ,则 [img=51x43]180349caea51829.png[/img] A: 0 B: 1 C: 2 D: 3
- 设 f(x)=1-2x,g(f(x))=(1-x)/x ,则 [img=51x43]180311a45a4ae1d.png[/img] A: 0 B: 1 C: 2 D: 3
- 设f''(x)在[0,2]连续,且f(0)=1,f(2)=3,f(2)=5,则。xf''(2x)dx=()。 A: 3 B: 2 C: 7 D: 6